„Spoliatus ante omnia restituendus est. Spuilzie” jako szkocka metoda restytucji utraconego posiadania - Szymura, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The author of the study tries to answer the question about the theory of the nature of possession in Scottish jurisprudence on the basis of the existing model of possessory protection. To this end he analyses spuilzie — a Scottish remedy to seek restitution, popular especially in the 17th and 18th centuries.He presents the views of the most important Scottish jurists, regarded as institutional writers of the day: James Dalrymple, Viscount of Stair; Andrew MacDougall, Lord Bankton; and John Erskine of Carnock. In addition, he presents the case law of Scotland’s Supreme Court (Court of Session) concerning the subject matter in question.The problems analysed by the author are as follows: the origins and ways of defining the legal basis of the remedy, its legal nature, capacity to sue, separate procedures and forms of defence employed by the sued party in spuilzie cases.
Keywords: prawo własności; posiadanie; prawo szkockie; spuilzie